Edukasi Latihan Fisik Meningkatkan Kesimbangan Pada Lansia - Citra Puspa Juwita; James Manik; Liswanto Dwi Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Elderly generally has an imbalance that is at risk of falling, it's related to joint stabilization and posture. Prodi Physiotherapy Team collaborated with the head of the Puskesmas of Kramat Jati and Camat Kramat Jati, East Jakarta conducted education to participants Forum Komunikasi Lansia Usia (FKLU). The purposed of the community service is the participant can practice physical exercises of treatment of balance disorders well and correctly. There are three stages in achieving the goal, namely the provision of education on balance, physical exercise prevention and self-management disorder imbalance training strategies, and simulation of assessment of the level of imbalances in 42 elderlies. Balance Strategy training includes three moves, namely strategic legs, strategic hips, and strategic steps. As a result of the evaluation, it was found that 93% of the participants could stand without a penetration, the balance of one leg was largely well balanced by the right leg, and at step movements the most balance was achieved when the right foot was in front. Beneficial Balance Strategy Training Increases the risk of falling on the elderly.